Notillage effects on soil properties and maize (Zea mays L. ) production in western Nigeria - Lal, R. (Springer, 1974)
The grain yields in the no-tillage plots were equivalent to those of conventionally plowed treatments. No-tillage treatments had higher organic matter content and, by controlling soil erosion, the silt and clay content than the plowed plots. The water holding capacity and moisture release characteristics of the surface soil horizon were significantly different for the two tillage treatments. A decrase in the maximum soil temperature and favourable moisture regime in the no-tillage plots stimulated biological activity e.g. earthworms. While the fertilizer had no response on the plowed plots, irrigation had a negative effect due probably to severe leaching losses. No-tillage techniques have a potential in achieving continuous cultivation on otherwise highly erodible and shallow tropical soils.